Health and Safety Communication in the Workplace: A Case Study of California Farmers - James I. Grieshop (Journal of Applied Communications, 1999)
This case study presents selected findings related to communication for agricultural health and safety of a convenience sample of California farmers. The overall purpose of the study was to document, analyze, and assess how agricultural operators conduct safety programs, seek and use safety-related information, and how they organize their operations to ensure a safe workplace. The study was carried out in the Fall, 1996, with the 662 safety award winners which comprise 5% of the 13,000 insured farmers throughout California. Responses from 137 respondents (20% response rate) indicate that while operators use a variety of information sources, they question the sources’ effectiveness and utility. A number of directions to follow in developing effective communication and education approaches that can impact the health and safety practices of California farmers are indicated. Results also indicate that new challenges for extension communicators and educators in the area of agricultural health and safety exist.